Mechanical Properties Of Glass Fibers Reinforced Composites: A Concise Review - et. al., Mitali Dugvekar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The utility of composites in today’s modern world is not hidden from anyone. From tiny objects like football to aerospace, everything involves the use of composites. Composites nearly form the backbone of our society. Composites are basically made from matrices and reinforcement. Out of the majority of reinforcement being used, Glass fibers usage cannot be neglected. These are made of fine fibers of glass (made of SiO2). They are used to reinforce various materials like arrows, bows and crossbows, translucent roofing panels, tent poles, boat hulls and paper honeycomb. This review paper is a study of various research papers related to mechanical properties of glass fibers when used with different type of matrices namely, tensile strength, impact strength and flexural strength.